(untitled) (Research, Society and Development, 2020)
The objective was to report the experience of nursing students regarding the realization of a health education action, referring to women’s health, in the context of a Family Health Strategy in Belém-PA. This is a qualitative study with a descriptive approach of the experience report type. As a theoretical and methodological foundation, the problematization methodology with the Arco de Maguerez was used, which is composed of five stages, namely: a) Observation of Reality; b) Survey of Key Points; c) Theorization; d) Solution hypotheses; e) Return to Reality. The tools used were: dynamics of myths and truths, where signboards were given to each participant to answer the questionnaires, a conversation wheel structured based on the questions used in the dynamics about breast cancer and preventive examination of cervical cancer. The instruments used had a good acceptability and active participation by the users, the participating public had previous knowledge of the subjects. However, pertinent points were elucidated and clarified in the face of the dialogue. Thus, it is necessary that there is a rapprochement between the nursing professional and the female population, thus, there may be exchanges of knowledge between them, contributing to the multiplication and transmission of information.